Effects of carnosine and vitamin E on Nucleobindin 2 (NUCB2)/nesfatin-1, ghrelin, adropin, and irisin in experimentally induced ovarian torsion - Sarac, Mehmet; Bakal, Unal; Kuloglu, Tuncay; Tartar, Tugay; Aydin, Suleyman; Yardim, Meltem; Kazez, Ahmet (Association of Clinical Scientists, 2018)
Introduction. Delay in the diagnosis of ovarian torsion leads to serious histopathological changes and many problems, including infertility. Various agents have been investigated to minimize detorsionassociated potential injury.This study was performed to study the effects of carnosine and vitamin E on tissue and serum expression of Nucleobindin 2 (NUCB2)/nesfatin-1, ghrelin, adropin, and irisin to determine whether they have protective effects in cases of ovarian torsion. Material and Method. Seventy-eight rats were allocated evenly into 13 groups. All rats, excluding those in the control and sham groups and Groups (G) III, IV, and V, were subjected to ovarian torsion for 12 hours. The groups were designated as follows: G-I (control), G-II (sham), G-III (vitamin E), G-IV (carnosine), G-V (carnosine + vitamin E), G-VI (torsion), G-VII (torsion + detorsion), G-VIII (torsion + vitamin E), G-IX (torsion + carnosine), G-X (torsion + carnosine + vitamin E), G-XI (torsion + detorsion + vitamin E), G-XII (torsion + detorsion + carnosine), and G-XIII (torsion + detorsion + carnosine + vitamin E). Serum levels of NUCB2/nesfatin-1, ghrelin, adropin, and irisin were measured by ELISA. Immunohistochemical methods were used to measure the expression of these hormones in ovarian tissue. Results.The levels of NUCB2/nesfatin-1 immunoreactivity were increased in G-VII, G-XI, and G-XII (p < 0.05).The immunoreactivity of ghrelin was significantly decreased in G-VI, G-IX, G-XI, and G-XII. However, adropin immunoreactivity did not differ significantly between the groups (p > 0.05). The level of irisin immunoreactivity was decreased in G-VI, G-VII, and G-VIII (p < 0.05).The serum levels of NUCB2/nesfatin-1, ghrelin, adropin, and irisin paralleled the tissue immunohistochemical results. Conclusion. Carnosine and vitamin E protected the ovaries from ischemiareperfusion injury in ovarian torsion.These antioxidants, especially carnosine, may be useful for the treatment of ovarian torsion. © 2018 by the Association of Clinical Scientists, Inc.
Keywords: Adropin; Carnosine; Ghrelin; Irisin; NUCB2/nesfatin-1; Ovarian torsion; Rat; Vitamin E